KEBIJAKAN INGGRIS TERHADAP MASALAH IMIGRAN UNI EROPA PASCA BREXIT TAHUN 2020 - Nisa, Salsabila Khairu; Iskandar, Irwan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
The UK's official membership of the European Union has brought several benefits such as the removal of barriers to exports and imports in the European Region. However, on the other hand, the European Union implemented a Free Movement of Person policy which resulted in the flow of EU immigrants in the UK becoming uncontrollable and affecting all aspects of the UK. Therefore, the UK decided to leave EU membership through the Brexit Referendum on 23 June 2016 and set a new immigrant policy, namely point-based and visa policies. This research uses the theory of foreign policy by Cristopher Hill which says foreign policy is influenced by external factors and internal factors. The perspective in this research is neorealism. The method used in this research is qualitative with literature study data collection techniques. The results show that the UK's decision to leave the European Union and implement a point-based immigrant policy and visa is due to external factors, namely 1) the EU's Free Movement of Person policy which is detrimental to the UK, 2) the presence of EU immigrants in the UK. And internal factors, namely 1) euroskepticism within British political parties, 2) the Brexit campaign. Keywords: Immigration, Brexit, European Union, UK